The calculators and Contents sections on this page require JavaScript but you appear to have switched JavaScript off
(it is disabled). Please go to the Preferences for this browser and enable it if you want to use the
calculators, then Reload this page.
As used here | Vajda | Dunlap | Knuth | Definition | Description |
Phi Φ |
τ | τ | φ, α |
= 1.6180339... | Koshy uses α (page 78)
|
phi φ | −σ | −φ | −β |
= 0.6180339... | Koshy uses −β (page 78)
|
abs(x) |x| | |x| | |x| | |x| | abs(x) = x if x≥0; abs(x) = −x if x<0 | the absolute value of a number, its magnitude; ignore the sign;
|
floor(x)
⌊x⌋
| [x] | trunc(x), not used for x<0 |
⌊x⌋ |
the nearest integer ≤ x. |
When x>0, this is "the integer part of x" or "truncate x"
i.e. delete any fractional part after the decimal point.
3=floor(3)=floor(3.1)=floor(3.9), -4=floor(-4)=floor(-3.1)=floor(-3.9) |
round(x) [x] |
[ x + |
1 | ] |
|
2 |
|
trunc(x + 1/2) |
|
the nearest integer to x; trunc(x+0.5) |
3=round(3)=round(3.1), 4=round(3.9),
-4=round(-4)=round(-3.9), -3=round(-3.1)
4=round(3.5), -3=round(-3.5)
|
ceil(x)
⌈x⌉
| - | - |
⌈x⌉
|
the nearest integer ≥ x. |
3=ceil(3), 4=ceil(3.1)=ceil(3.9), -3=ceil(-3)=ceil(-3.1)=ceil(-3.9) |
fract(x) frac(x) | - | - |
x mod 1 | x − floor(x) |
the fractional part of x, i.e. the part of abs(x) after the decimal point
|
|
|
|
|
|
nCr n choose r; the element in row n column r of
Pascal's Triangle the coefficient of xr in (1+x)n
the number of ways of choosing r objects from a set of n different objects.
n≥0 and r≥0 (otherwise value is 0)
|
Formula | Refs | Comments |
F(0) = 0, F(1) = 1, F(n+2) = F(n + 1) + F(n) | - | Definition of the Fibonacci series |
F(−n) = (−1)n + 1 F(n) | Vajda-2, Dunlap-5 | Extending the Fibonacci series 'backwards' |
L(0) = 2, L(1) = 1, L(n + 2) = L(n + 1) + L(n) | - | Definition of the Lucas series |
L(−n) = (−1)n L(n) | Vajda-4, Dunlap-6 | Extending the Lucas series 'backwards' |
G(n + 2) = G(n + 1) + G(n) | Vajda-3, Dunlap-4 | Definition of the Generalised Fibonacci series, G(0) and G(1) needed |
|
Dunlap-63 |
Phi and −phi are the roots of x2 = x + 1
|
|
Dunlap-65 |
Beware! Dunlap occasionally uses φ to
represent our phi = 0.61803.., but more frequently he uses
φ to represent −0.61803.. !
|
|
F(n + 2) + F(n) + F(n − 2) = 4 F(n) | B&Q(2003)-Identity 18 |
F(n + 2 ) + F(n) = L(n + 1) | by Definition of L(n), Vajda-6, Hoggatt-I8, B&Q(2003) Identity 32, Dunlap-14, Koshy-5.14 |
F(n + 2) − F(n) = F(n + 1) | by Definition of F(n) |
F(n + 3) + F(n) = 2 F(n + 2) | B&Q(2003)-Identity 16 |
F(n + 3) − F(n) = 2 F(n + 1) | - |
F(n + 4) + F(n) = 3 F(n + 2) | B&Q(2003)-Identity 17 |
F(n + 2) + F(n − 2) = 3 F(n) | B&Q(2003)-Identity 7 |
F(n + 2) − F(n − 2) = L(n) | Hoggatt-I14 |
F(n + 4) − F(n) = L(n + 2) | - |
F(n + 5) + F(n) = F(n + 2) + L(n + 3) | - |
F(n + 5) − F(n) = L(n + 2) + F(n + 3) | - |
F(n + 6) + F(n) = 2 L(n + 3) | - |
F(n + 6) − F(n) = 4 F(n + 3) | - |
F(n) + 2 F(n − 1) = L(n) | (Dunlap-32), B&Q(2003) Identity 50 |
F(n + 2) − F(n − 2) = L(n) | Vajda-7a, Dunlap-15, Koshy-5.15 |
F(n + 3) − 2 F(n) = L(n) | possible correction for Dunlap-31 |
F(n + 2) − F(n) + F(n − 1) = L(n) | possible correction for Dunlap-31 |
F(n) + F(n + 1) + F(n + 2) + F(n + 3) = L(n + 3) | C Hyson(*) |
| "Binet's" Formula
De Moivre(1718), Binet(1843), Lamé(1844),
Vajda-58, Dunlap-69, Hoggatt-page 11, B&Q(2003)-Identity 240 |
L(n) = Phin + (−phi)n |
Vajda-59, Dunlap-70, B&Q(2003)-Identity 241 |
Phin = Phi F(n) + F(n−1) |
Vajda-50a, Rabinowitz-28, B&Q(2003)-Corrolary 33 |
Phin = F(n+1) + F(n) phi | Rabinowitz-28, B&Q(2003)-Corollary 33 |
|
Vajda-50b, Rabinowitz-25, B&Q(2003)-Identity 242,
I Ruggles (1963) FQ 1.2 pg 80 |
(−phi)n = |
L(n) − F(n)√5 |
2 |
|
Vajda-50c, I Ruggles (1963) FQ 1.2 pg 80,
Rabinowitz-25, B&Q(2003)-Identity 243 |
(−phi)n = −phi F(n) + F(n−1) | Rabinowitz-28 |
(−phi)n = F(n+1) − Phi F(n) | Vajda-103b, Dunlap-75 |
√5 Phin = Phi L(n) + L(n−1) | - |
√5 (−phi)n = phi L(n) − L(n−1) | - |
|
Vajda-101 |
|
Vajda-101a |
F(n) = round | ( |
Phin |
) |
,if n≥0 |
|
√5 |
| Vajda-62, Dunlap-71 corrected, B&Q(2003)-Identity 240 Corollary 30 |
L(n) = round(Phin),if n≥2 | Vajda-63, Dunlap-72, B&Q(2003)-Corollary 35 |
F(−n) = round |
( |
|
) |
,if n≥0 |
| - |
L(−n) = round( (−phi)−n ), n≥2 | - |
F(n + 1) = round(Phi F(n)),if n≥2 | Vajda-64, Dunlap-73 |
L(n + 1) = round(Phi L(n)),if n≥4 | Vajda-65, Dunlap-74 |
fract( F(2n) phi ) = 1 − phi2n | Knuth vol 1, Ex 1.2.8 Qu 31 with ψ=phi |
fract( F(2n+1) phi ) = phi2n+1 | Knuth vol 1, Ex 1.2.8 Qu 31 |
F(nk) is a multiple of F(n)
F(nk) ≡ 0 (mod F(k)) | B&Q(2003)-Theorem 1, Vajda Theorem I page 82 |
gcd(F(m),F(n)) = F(gcd(m,n)) | Lucas (1878) B&Q(2003)-Theorem 6,Vajda Theorem II page 83 |
F(mn+r) ≡ ± F(r) (mod F(n) ) | Knuth Vol 1 Ex 1.2.8 Qu. 32, Vajda page 86 |
gcd(L(m),L(n)) = L(gcd(m,n)),
if both L(m)/gcd(L(m),L(n)) and
L(n)/gcd(L(m),L(n)) are odd integers | Vajda page 86 |
L(mn+r) ≡ ± L(r) (mod L(n) ) | (Vajda page 87) |
F(m q) | = | F(m) | | F(m - 1) j-1 | F( m(q - j) + 1 ) |
|
| B&Q(2003)-Theorem 2 |
F(kt) | | F(t) |
| = | | + (−1)(k−1)t/2 for ODD k ≥ 3 |
| Vajda-85 |
F(kt) | | F(t) |
| = | | for EVEN k ≥ 2 |
| Vajda-86 |
L(kt) | | L(t) |
| = | | + (−1)(k−1)(t+1)/2 for ODD k ≥ 3 |
| Vajda-87 |
L(t) is not a factor of L(kt) for even k | |
F(kt) | | L(t) |
| = | | for EVEN k ≥ 2 |
| Vajda-88 |
L(t) is not a factor of F(kt) for odd k and t≥3 | |
p prime ⇒ p is a factor of L(p) − 1 |
B&Q(2003) Identity 228 |
p prime ⇒ p is a factor of L(2p) − 3 |
B&Q(2003) Identity 229 |
F(2n) = F(n + 1)2 − F(n − 1)2 | Lucas(1878), B&Q(2003)-Identity 14, Hoggatt-I10 |
F(2n) = F(n) ( F(n+1) + F(n−1) ) | Vajda-13, Hoggatt-I7, Koshy-5.13, B&Q(2003)-Identity 33
with Vajda-6 |
F(2n) = F(n) (2F(n+1) − F(n)) | simple alternative to Vajda-13 |
F(2n+1) = F(n + 1)2 + F(n)2 | Vajda-11, Dunlap-7, Lucas(1878), B&Q(2003)-Identity 13, Hoggatt-I11 |
F(n+2)2 + F(n)2 = 3 F(n + 1)2 − 2 (−1)n | V E Hoggatt B-208 FQ 9 (1971) pg 217. |
F(n+3)2 + F(n)2 = 2 ( F(n+1)2 + F(n+2)2 ) | B&Q(2003)-Identity 30 |
F(n + k + 1)2 + F(n − k)2 = F(2k + 1)F(2n + 1) | Sharpe(1965), a generalization of Vajda-11,Dunlap-7
Melham(1999) |
F(n + k)2 + F(n − k)2 =F(n + k −2)F(n + k + 1) + F(2k − 1)F(2n − 1) | Sharpe (1965) |
F(n + 1)2 − F(n)2 = F(n + 2) F(n − 1) | Vajda-12, Dunlap-8 |
F(n + k + 1)2 − F(n − k)2 = F(n − k − 1)F(n − k + 2) + F(2 k)F(2n + 2) | Sharpe (1965) |
F( n+p )2 − F( n−p )2 = F( 2n )F( 2p ) |
I Ruggles (1963) FQ 1.2 pg 77; Hoggatt-I25, Sharpe (1965) |
F(n + 1) F(n − 1) − F(n)2 = (−1)n |
Cassini's Formula(1680), Simson(1753), Vajda-29, Dunlap-9, Hoggatt-I13
special case of Catalan's Identity with r=1
B&Q(2003)-Identity 8 |
F(n)2 − F(n + r)F(n − r) = (-1)n-rF(r)2 |
Catalan's Identity(1879) |
F(n)F(m + 1) − F(m)F(n + 1) = (-1)mF(n − m) |
d'Ocagne's Identity, special case of Vajda-9 with G=F |
F(n + m) = F(n + 1)F(m + 1) − F(n − 1)F(m − 1) | B&Q(2003)-Identity 231 |
F(n + m) = F(m) F(n + 1) + F(m − 1) F(n) | alternative to Dunlap-10, B&Q(2003)-Identity 3;
variation of Hansen (1972)
Vorob'ev (1951) pages 9-10 proof, attributed to I S Sominskii
|
F(n) = F(m) F(n + 1 − m) + F(m − 1) F(n − m) |
I Ruggles (1963) FQ 1.2 pg 79; Dunlap-10, special case of Vajda-8 |
F(n) F(n + 1) = F(n − 1) F(n + 2) + (−1)n-1 |
Vajda-20a special case: i:=1;k:=2;n:=n-1; Hoggatt-I19 |
F(n + i) F(n + k) − F(n) F(n + i + k) = (−1)n F(i) F(k) |
Vajda-20a=Vajda-18 (corrected) with G:=H:=F |
2 F(n + 1) = F(n) + √(5 F(n)2 + 4(−1)n)
| F(n+1) from F(n): Problem B-42, S Basin, FQ, 2 (1964) page 329 |
F(a)F(b) − F(c)F(d) = (−1)r( F(a − r)F(b − r) − F(c − r)F(d − r) )
a+b=c+d for any integers a,b,c,d,r |
Johnson FQ 42 (2004) B-960 'A Fibonacci Iddentity', solution pg 90
also Johnson-7
Cassini, Catalan and D'Ocagne's Identities
are all special cases of this formula |
L(n + 2)2 = 3 L(n + 1)2 − L(n)2 + 10(−1)n | V E Hoggatt B-208 FQ 9 (1971) pg 217. |
L(n + 2) L(n − 1) = L(n + 1)2 − L(n)2 | from Vajda-17a |
L(n + 1)2 + L(n)2 = L(2n) + L(2n + 2) | from Vajda-17a |
L(n + 1)2 − L(n − 1)2 = L(2n + 1) + L(2n − 1) | from Vajda-17a |
L(n + 1) L(n − 1) − L(n)2 = −5 (−1)n | B&Q(2003)-Identity 60 |
L(2n) + 2 (−1)n = L(n)2 | Vajda-17c, Dunlap-12, B&Q(2003)-Identity 36 |
L(n + m) + (−1)m L(n − m) = L(m) L(n) | Vajda-17a, Dunlap-11
(special cases: Hoggatt-I15,I18) |
L(4n) + 2 = L(2n)2 | Hoggatt-I15, special case of Vajda-17a |
2 L(n + 1) = L(n) + √5 √(L(n)2 − 4(−1)n)
| L(n+1) from L(n): Problem B-42, S Basin, FQ 2 (1964) page 329 |
F(2n) = F(n) L(n) | Vajda-13, Hoggatt-I7, Koshy-5.13, B&Q(2003)-Identity 33 |
F(4n) | + 1 = | F(2n−1) L(2n+1) |
F(4n+1) | + 1 = | F(2n+1) L(2n) |
F(4n+2) | + 1 = | F(2n+2) L(2n) |
F(4n+3) | + 1 = | F(2n+1) L(2n+2) |
|
F(n)+1 is a product of a FIbonacci and a Lucas number:
A001611 F(n)+1, Formula by R K Guy (2003)
|
5 F(n) = L(n + 1) + L(n − 1)
|
L(n + 1)2 + L(n)2 = 5 F(2n + 1) | Vajda-25a |
L(n + 1)2 − L(n − 1)2 = 5 F(2n) | - |
L(n + 1)2 − 5 F(n)2 = L(2n + 1) | - |
L(2n) − 2 (−1)n = 5 F(n)2 | Vajda-23, Dunlap-25 |
L(n)2 − 4(−1)n = 5 F(n)2 | B&Q(2003)-Identity 53, Hoggatt-I12 |
F(n+k) + (−1)k F(n−k) = F(n)L(k) | Bro U Alfred (1964), Bergum and Hoggatt (1975) equns (5),(7) |
F(n+k) − (−1)k F(n−k) = L(n)F(k) | Bro U Alfred (1964), Bergum and Hoggatt (1975) equns (6),(8) |
L(n+k) + (−1)k L(n−k) = L(n)L(k) | Bro U Alfred (1964), Bergum and Hoggatt (1975) equns (9),(11) |
L(n+k) − (−1)k L(n−k) = 5F(n)F(k) | Bro U Alfred (1964), Bergum and Hoggatt (1975) equns (10),(12) |
F(n + 1) L(n) = F(2n + 1) + (−1)n | Vajda-30, Vajda-31, Dunlap-27, Dunlap-30 |
L(n + 1) F(n) = F(2n + 1) − (−1)n | - |
F(2n + 1) = F(n + 1) L(n + 1) − F(n) L(n) | Vajda-14, Dunlap-18 |
L(2n + 1) = F(n + 1) L(n + 1) + F(n) L(n) | - |
L(m) L(n) + L(m − 1) L(n − 1) = 5 F(m + n − 1) | Hansen 1972 |
L(n)2 − 2 L(2n) = −5 F(n)2 | Vajda-22, Dunlap-24 |
5 F(n)2 − L(n)2 = 4 (−1)n + 1 | Vajda-24, Dunlap-26 |
F(n)2 + L(n)2 = 4 F(n + 1)2 − 2 F(2n) | FQ (2003)vol 41, B-936, M A Rose, page 87 |
5 (F(n)2 + F(n + 1)2) = L(n)2 + L(n + 1)2 | Vajda-25 |
F(n) L(m) = F(n + m) + (−1)m F(n − m) | a recurrence relation for F(n+km): Vajda-15a, Dunlap-19 |
L(n) F(m) = F(n + m) − (−1)m F(n − m) | Vajda-15b, Dunlap-20 |
5 F(m) F(n) = L(n + m) − (−1)m L(n − m) | Vajda-17b, Dunlap-23, (special cases:Hoggatt-I16,I17) |
2 F(n + m) = L(m) F(n) + L(n) F(m) | Vajda-16a, Dunlap-2, FQ (1967) B106 H H Ferns pp 466-467 |
2 L(n + m) = L(m) L(n) + 5 F(n) F(m) | FQ (1967) B106 H H Ferns pp 466-467 |
F(m) L(n) + F(m − 1) L(n − 1) = L(m + n − 1) | Hansen (1972) |
(−1)m 2 F(n − m) = L(m) F(n) − L(n) F(m) | Vajda-16b, Dunlap-22 |
L(n + i) F(n + k) − L(n) F(n + i + k) =
(−1)n + 1 F(i) L(k) | Vajda-19a |
F(n + i) L(n + k) − F(n) L(n + i + k) = (−1)n F(i) L(k) | Vajda-19b |
L(n + k + 1)2 + L(n − k)2 = 5 F(2n + 1)F(2k + 1) |
Melham (1999) Theorem 1 |
L(n + i) L(n + k) − L(n) L(n + i + k)
= (−1)n + 1 5 F(i) F(k) | Vajda-20b |
(−1)kF(n)F(m−k) + (−1)mF(k)F(n−m) + (−1)nF(m)F(k−n) = 0 |
FQ 11 (1973) B228 page 108 |
(−1)kL(n)F(m−k) + (−1)mL(k)F(n−m) + (−1)nL(m)F(k−n) = 0 |
FQ 11 (1973) B229 page 108 |
5 F(jk+r) F(ju+v) = L(j(k+u)+(r+v)) - (-1)ju+vL(j(k-u)+(r-v)) |
Hansen (1978) |
F(jk+r) L(ju+v) = F(j(k+u)+(r+v)) + (-1)ju+vF(j(k-u)+(r-v)) |
Hansen (1978) |
L(jk+r) L(ju+v) = L(j(k+u)+(r+v)) + (-1)ju+vL(j(k-u)+(r-v)) |
Hansen (1978) |
5F(a)F(b) − L(c)L(d) = (−1)r( 5F(a − r)F(b − r) − L(c − r)L(d − r) )
a+b=c+d for any integers a,b,c,d,r |
Johnson |
F(a) L(b) − F(c) L(d) = (−1)r( F(a−r) L(b−r) − F(c−r) L(d−r) with a+b=c+d |
Johnson-32, special case of Johnson-44 |
F(3n) = F(n + 1)3 + F(n)3 − F(n − 1)3 |
Lucas (1876), B&Q(2003)-Identity 232 |
5 L(3n) = L(n + 1)3 + L(n)3 − 3 L(n − 1)3 |
Long (1986) equation (45)
|
3 F(3n) = F(n+2)3 − 3 F(n)3 + F(n−2)3 |
J Ginsburg "A Relationship Between Cubes
of Fibonacci Numbers."
Scripta Mathematica (1953) page 242. |
L(3n) = L(n+1)F(n+1)2 + L(n)F(n)2 − L(n-2)F(n-1)2) |
Long (1986) equation (43) |
5 F(3n) = F(n+1)L(n+1)2 + F(n)L(n)2 − F(n-1)L(n-1)2 |
Long (1986) equation (44) |
F(n + 1)F(n + 2)F(n + 6) − F(n + 3)3 = (−1)nF(n)
F(n)F(n + 4)F(n + 5) − F(n + 3)3 = (−1)n+1F(n + 6)
|
FQ 41 (2003) pg 142, Melham.
The second is a variant with -n for n and using Vajda-2 |
|
F(n−2)F(n−1)F(n+3) − F(n)3 = (−1)n-1F(n−3)
F(n+2)F(n+1)F(n−3) − F(n)3 = (−1)nF(n+3)
| Fairgrieve and Gould (2005) versions of the above two formulae of Melham |
F(n−2)F(n+1)2 − F(n)3 = (−1)n-1 F(n−1)
F(n+2)F(n−1)2 − F(n)3 = (−1)n F(n+1)
| Fairgrieve and Gould (2005) |
F(n+a+b)F(n−a)F(n−b) − F(n-a-b)F(n+a)F(n+b)
= (−1)n+a+bF(a)F(b)F(a+b)L(n)
| Melham (2011) Theorem 1 |
F(n+a+b−c)F(n−a+c)F(n−b+c) − F(n−a−b+c)F(n+a)F(n+b)
= (−1)n+a+b+cF(a+b−c)( F(c)F(n+a+b−c)
+ (−1)cF(a−c)F(b−c)L(n) ) |
Melham (2011) Theorem 5 |
F(i+j+k) = F(i+1)F(j+1)F(k+1) + F(i)F(j)F(k) − F(i−1)F(j−1)F(k−1)
for any integers i,j,k
| Johnson's (6) |
F(3n) = F(n+1)3 + F(n)3 − F(n−1)3 | From Johnson's (6) with i=j=k |
F(n)3 = F(n−1)3 + F(n−2)3 + 3 F(n)F(n−1)F(n−2) |
G Gelatti (2020, private communication) |
L(5n) = L(n) (L(2n) + 5F(n) + 3)( L(2n) − 5F(n) + 3), n odd |
Aurifeuille's Identity (1879) FQ 42 (2004) R S Melham, pgs 155-160 |
F(4n) = F(n+1)4 + 2F(n)4 − F(n−1)4 + 4F(n)3F(n−1)
| Khomovsky (2018) A42 |
F(n−1)2F(n+1)2 − F(n−2)2F(n+2)2
= 4(−1)nF(n)2 |
Melham (2011) 21 |
F(n−3)F(n−1)F(n+1)F(n+3) − F(n)4
= (−1)nL(n)2 |
Melham (2011) 22 |
F(n)2 F(m + 1) F(m − 1) − F(m)2 F(n + 1) F(n − 1)
= (−1)n − 1 F(m + n) F(m − n) | Vajda-32 |
F(n − 2)F(n − 1)F(n + 1)F(n + 2) + 1 = F(n)4
| Gelin-Cesàro Identity (1880) (see Dickson page 401)
FQ 41 (2003) pg 142, B&Q(2003)-Identity 31 Hoggatt-I29, Simson(1753) |
L(n − 2)L(n − 1)L(n + 1)L(n + 2) + 25 = L(n)4 | B&Q(2003)-Identity 56 |
F(n+a+b+c)F(n−a)F(n−b)F(n−c) − F(n-a-b-c)F(n+a)F(n+b)F(n+c)
= (−1)n+a+b+cF(a+b)F(a+c)F(b+c)F(2n)
| Melham (2011) Theorem 2 |
F(n+a+b+c−d)F(n−a+d)F(n−b+d)F(n−c+d)
−
F(n−a−b−c+2d)F(n+a)F(n+b)F(n+c)
= (−1)n+a+b+cF(a+b−d)F(a+c−d)F(b+c−d)F(2n+d) |
Melham (2011) Theorem 6 |
( F(n-1)F(n+2) )2 + (2 F(n)F(n+1) )2
= (F(n+1)F(n+2) − F(n-1)F(n))2
= F(2n+1)2 |
A F Horadam FQ 20 (1982) pgs 121-122, B&Q(2003)-Identity 19 (corrected)
special case of Generalised Fibonacci Pythagorean Triples |
( F(n)2 + F(n+1)2 + F(n+2)2 )2
= 2 ( F(n)4 + F(n+1)4 + F(n+2)4 )
| Candido's Identity (1951)
FQ 42 (2004) R S Melham, pgs 155-160
|
( L(n-1)L(n+2) )2 + ( 2L(n)L(n+1) )2
= ( 5F(2n+1) ) 2 |
Wulczyn FQ 18 (1980) pg 188
special case of Generalised Fibonacci Pythagorean Triples |
( |
|
) |
F |
= F(m − 1) |
( |
|
) |
F |
+ F(n + 1) |
( |
|
) |
F |
|
Vajda page 74, "add the two numbers above" analogy from Pascal's triangle |
|
(-1)j(j+3)/2 |
|
F(n+m−j)m+1 |
= F!(m) F((m+1)n+m(m+1)
/2)) |
| Melham (1999).... |
1 F(n+1)2 + 1 F(n)2 | = 1 | F(2n+1) |
1 F(n+2)3 + 1 F(n+1)3 −1 F(n)3 | = 1.1 | F(3n+3) |
1 F(n+3)4 + 2 F(n+2)4 −2 F(n+1)4 − 1 F(n)4 | = 1.1.2 | F(4n+6) |
1 F(n+4)5 + 3 F(n+3)5 −6 F(n+2)5 −3 F(n+1)5 + 1 F(n)5 | = 1.1.2.3 | F(5n+10) |
1 F(n+5)6 + 5 F(n+4)6 −15 F(n+3)6 −15 F(n+2)6 + 5 F(n+1)6 + 1 F(n)6 | = 1.1.2.3.5 | F(6n+15) |
| .... examples |
0 = F(n) − F(n−1) − F(n−2)
0 = F(n)2 − 2 F(n−1)2 − 2 F(n−2)2 + F(n−3)2
0 = F(n)3 − 3 F(n−1)3 − 6 F(n−2)3 + 3 F(n−3)3 + F(n−4)3
0 = F(n)4 − 5 F(n−1)4 − 15 F(n−2)4 + 15 F(n−3)4 + 5 F(n−4)4 − F(n−5)4
... | Brousseau (1968)...but the general formula was not given. For this see next line: |
| Knuth AoCP Vol 1 section 1.2.8 Exercise 30, (1997)
|
| compare with |
| = | n − k + 1 | | k |
| |
|
|
|
|
|
|
|
|
G(n) = G(0) F(n − 1) + G(1) F(n) | B&Q(2003)-Identity 37 |
G(−n) = (−1)n (G(0) F(n + 1) − G(1) F(n)) | ditto - applying Vajda-2 or
Vajda-9 with n=0 |
√5 G(n) = ( G(0) phi + G(1) ) Phin + (G(0) Phi − G(1)) ( −phi )n |
Vajda-55/56, Dunlap-77, B&Q(2003)-Identity 244 |
F(n) = | G(0) G(n+1) − G(1) G(n) |
G(0)G(2) − G(1)2 |
|
| Amer Math Monthly (2005) "Fibonacci, Chebyshev and Orthogonal Polynomials"
D Aharonov, A Beardam, K Driver, p612-630 |
2 G(k) = ( 2 G(1) − G(0) ) F(k) + G(0) L(k) |
Johnson-46 |
G(n + m) = F(m − 1) G(n) + F(m) G(n + 1) | Vajda-8, Dunlap-33, B&Q(2003)-Identity 38, Johnson-40 |
G(n − m) = (−1)m (F(m + 1) G(n) − F(m) G(n + 1)) | Vajda-9, Dunlap-34,
B&Q(2003)-Identity 47 |
G(n + m) + (−1)m G(n − m) = L(m) G(n) | Vajda-10a, Dunlap-35, B&Q(2003)-Identity 45, Bergum & Hoggatt (1975) (36) and (38) |
G(n + m) − (−1)m G(n − m) = F(m) ( G(n−1) + G(n+1)) | Vajda-10b, Dunlap-36, B&Q(2003)-Identity 48, Bergum & Hoggatt (1975) (37) and (39) |
G(m) F(n) − G(n) F(m) = (−1)n+1 G(0) F(m − n) | Vajda-21a |
G(m) F(n) − G(n) F(m) = (−1)m G(0) F(n − m) | Vajda-21b |
G(m+k) F(n+k) + (−1)k+1 G(m) F(n) = F(k) G(m + n + k) | Howard(2003) |
G(n + i) H(n + k) − G(n) H(n + i + k)
= (−1)n (G(i) H(k) − G(0) H(i + k)) |
Vajda-18 (corrected), B&Q(2003)-Identity 44 (also Identity 68)
a special case of Johnson-44: |
G(p)H(q) − G(r)H(s)
= (-1)n[ G(p-n)H(q-n) − G(r-n)H(s-n) ]
if p+q = r+s and p,q,r,s,n are integers |
Johnson-44 |
G(n + 1) G(n − 1) − G(n)2 = (−1)n (G(1)2 − G(0) G(2)) |
Vajda-28, B&Q(2003)-Identity 46 |
4 G(n−1)G(n) + G(n−2)2 = G(n+1)2 | B&Q(2003)-Identity 65 |
G(n + 3)2 + G(n)2 = 2( G(n+1)2 + G(n+2)2 ) |
B&Q(2003)-Identity 70 |
G(i+j+k) = F(i+1)F(j+1)G(k+1) + F(i)F(j)G(k) − F(i−1)F(j−1)G(k−1)
for any integers i,j,k
| Johnson (39a) |
4G(i)2G(i+1)2 + G(i−1)2G(i+2)2
= ( G(i)2 + G(i+1)2 )2 | Generalised Fibonacci Pythagorean Triples
Horadam (1967) |
G(n + 2)G(n + 1)G(n − 1)G(n − 2) + ( G(2)G(0) − G(1)2 )2
= G(n)4 |
B&Q(2003)-Identity 59 |
|
Hoggatt-I1, Lucas(1878), B&Q 2003-Identity 1 |
|
(-1) i F(i) = (-1)n F(n − 1) − 1 |
|
B&Q 2003-Identity 21 |
|
Hoggatt-I2 |
|
F(i) = F(n + 2) − F(a + 1) |
|
- |
|
L(i) = L(n + 2) − L(a + 1) |
|
- |
|
F(2i) = F(2n + 1) − 1, n≥0 |
|
Hoggatt-I6, Lucas(1878), B&Q(2003)-Identity 12 |
|
Hoggatt-I5, Lucas(1878), B&Q(2003)-Identity 2 |
| - |
|
2n − i F(i − 1) = 2n − F(n + 2) |
|
Vajda-37a(adapted), Dunlap-42(adapted), B&Q(2003)-Identity 10 |
|
B&Q(2003)-Identity 236 |
| = | F(3n + 3) | | 2 |
|
| B&Q(2003)-Identity 23 |
| = | F(3n + 4) − 1 | | 2 |
|
| B&Q(2003)-Identity 24 (corrected) |
| = | F(3n + 2) − 1 | | 2 |
|
| B&Q(2003)-Identity 25 (corrected) |
|
B&Q 2003-Identity 27 |
|
F(4i + 1) = F(2n + 1)F(2n + 2) |
|
B&Q 2003-Identity 26 |
|
F(4i + 2) = F(2n + 1)F(2n + 3) − 1 |
|
B&Q 2003-Identity 29 |
|
F(4 i + 3) = F(2n + 3)F(2n + 2) |
|
B&Q 2003-Identity 28 |
|
(−1)i L(n − 2i) = 2 F(n + 1) |
|
Vajda-97, Dunlap-54 |
|
(−1)i L(2n − 2i + 1) = F(2 n + 2) |
|
B&Q(2003)-Identity 55 |
|
Vajda-45, Dunlap-5, Hoggatt-I3, Lucas(1878), Koshy-77,
B&Q(2003)-Identity 9 (Identity 233 variant) |
|
L(i)2 = L(n) L(n + 1) − 2 |
|
Hoggatt-I4 |
|
L(i)2 = 5 F(2n) F(2n - 1) |
|
- |
|
Vajda-40, Dunlap-45 |
|
L(i) L(i − 1) = L(2n)2 − 4 |
|
- |
|
F(i) F(i − 1) = F(2n +1)2 − 1 |
|
Vajda-42, Dunlap-47 |
|
L(i) L(i − 1) = L(2n +1)2 − 1 |
|
- |
|
(−1)r(1+k) F(r(1+k))2 = (−1)r(n+1) |
|
− 2n − 3 | |
Vajda-93 |
|
(−1)r(1+k) L(r(1+k))2 = (−1)r(n+1) |
|
+ 2n + 1 | |
Vajda-94 |
|
Vajda-95, B&Q(2003)-Identity 234 |
|
Vajda page 70 |
|
Vajda-96, B&Q(2003)-Identity 54 |
|
L(2i)2 = F(4n + 2) + 2n − 1 |
|
Vajda page 70 |
5 |
|
F(i) F(n − i) |
|
= (n + 1) L(n) − 2 F(n + 1) |
= n L(n) − F(n) |
|
|
Vajda-98, Dunlap-55, B&Q(2003)-Identity 58 |
|
L(i) L(n − i) |
|
= (n + 1) L(n) + 2 F(n + 1) |
= (n + 2) L(n) + F(n) |
|
|
Vajda-99, Dunlap-56, B&Q(2003)-Identity 57 |
|
F(i) L(n − i) = (n + 1) F(n) |
|
Vajda-100, Dunlap-57, B&Q(2003)-Identity 35 |
|
V Hoggatt (1965) Problem B-53 FQ 3, pg 157 |
|
L G Brökling (1964) FQ 2.1 Problem B-20 solution, pg76;
Vajda-33; Dunlap-38; B&Q(2003)-Identity 39 |
|
G(i) = G(n + 2) − G(a + 1) |
|
- |
|
Vajda-34, Dunlap-37, B&Q(2003)-Identity 61 |
|
Vajda-35, Dunlap-39, B&Q(2003)-Identity 62 |
|
G(2i) − |
|
G(2i − 1) = |
|
(−1)iG(i) |
= |
G(2n − 1) + G(0) − G(1) |
|
Vajda-36, Dunlap-40 |
|
G(k − 1) 2−k |
= ( G(0) + G(3) )/2 − G(n + 2) 2−n |
|
Vajda-37, Dunlap-41, B&Q(2003)-Identity 69 |
|
G(i) = L(2n + 1) G(2n + 3) |
|
Vajda-38, Dunlap-43, B&Q(2003)-Identity 49 |
|
G(i) G(i − 1) = G(2n)2 − G(0)2 |
|
Vajda-39, Dunlap-44, B&Q(2003)-Identity 41 |
|
G(i) G(i − 1) = G(2 n + 1)2 − G(0)2 − G(1)2 + G(0)G(2) |
|
Vajda-41, Dunlap-46 |
|
G(i + 2) G(i − 1) = G(n + 1)2 − G(1)2 |
|
Vajda-43, Dunlap-48, B&Q(2003)-Identity 64 |
(1 + (−1)r − L(r) ) |
|
G(m + kr) = |
|
G(m) − G(m+(n+1)r) + (−1)r(G(m+nr) − G(m−r))
|
|
Fibonacci with a Golden Ring Kung-Wei Yang
Mathematics Magazine 70 (1997), pp. 131-135. |
|
G(i)2 = G(n) G(n + 1) − G(0) G(1) |
|
Vajda-44, Dunlap-49, B&Q(2003)-Identity 67 |
|
Stan Rabinowitz, "Second-Order Linear Recurrences" card, Generating Function
special case (x=1/r, P=1, Q=-1) |
|
|
| r (b r2 − 2 a r + b − a) |
= |
(r2 − r − 1)2 |
|
|
- |
| = | G ( 2n ) H( 2n − 1) − G(0) H(1) |
| B&Q(2003)-Identity 42 |
|
B&Q(2003) Identity-4 |
|
Vajda-54(corrected), Dunlap-84(corrected) |
|
B&Q(2003)-Identity 165 |
|
B&Q(2003)-Identity 166 |
|
S Basin & V Ivanoff (1963) Problem B-4, FQ 1.1 pg 74, FQ1.2 pg 79; B&Q(2003)-Identity 6 |
|
I Ruggles (1963) FQ 1.2 pg 77 |
|
I Ruggles (1963) FQ 1.2 pg 77 |
|
B&Q(2003)-Identity 20 |
|
B&Q(2003)-Identity 238, Vajda-68, Griffiths (2013) 8-corrected |
|
(−1)n−k |
|
2kF(2 k) = F(3 n) |
|
Griffiths (2013) page 239-corrected |
|
Griffiths (2013) |
|
Griffiths (2013) page 239 |
|
Vajda-50, Dunlap-82 |
|
Hoggatt-I41 (special case p=0: Vajda-69, Dunlap-85) |
|
Vajda-71, Dunlap-87 |
|
|
F(2i + p) = 5n L(2n + 1 + p) |
|
Hoggatt-I42 (special case p=0: Vajda-70, Dunlap-86) |
|
Vajda-72, Dunlap-88 |
|
Vajda-73, Dunlap-89,Hoggatt-I45 |
|
Vajda-75, Dunlap-91, Hoggatt-I46 |
|
Vajda-74, Dunlap-90, Hoggatt-I47 |
|
Vajda-76, Dunlap-92 |
|
Vajda-91, B&Q(2003)-Identity 235, Catalan 1857 |
|
Vajda-92, B&Q(2003)-Identity 237, Catalan (1857)-see Vajda pg 69 |
|
|
F(n)iF(n−1)k − iF(i) = F( kn ) |
|
Rabinowitz-17 (special case of Vajda-66) |
|
|
F(n)iF(n−1)k − iL(i) = L( kn ) |
|
Rabinowitz-17 (special case of Vajda-66) |
|
|
F(t)iF(t−1)p − iG( m+i ) = G( m+tp ) |
|
Vajda-66,B&Q(2003) Identity-11 |
|
B&Q(2003) Identity 5 |
|
= |
|
(−1)k(r−1) |
|
L(r)n − 1 − 2k |
| |
Lucas (1878) equations 74-76,
this form due to Hoggatt and Lindt (1969), see Gould (1977)
|
|
Griffiths (2013) |
sin( π/2 + i ln(Φ) ) = (√5)/2 = Φ + ½ |
Schroeder 1986, equation (5.41) page 68 |
|
D Lind, Problem H-64, FQ 3 (1965), page 116 |
F(n) = |
2 i 1−n |
sin(−i n ln( i Phi) ) |
√5 |
| from Rabinowitz-7 corrected, using
Phi2 = (√5 + 1)/(√5 − 1) |
F(n) = |
2 i −n |
sinh(n ln( i Phi) ) |
√5 |
| from Rabinowitz-7 corrected |
L(n) = 2 i −n cos(−i n ln( i Phi) ) |
from Rabinowitz-7 corrected |
L(n) = 2 i −n cosh( n ln( i Phi) ) |
from Rabinowitz-7 corrected |
√ | 1 + 2i | = √Phi + i √phi |
|
| = [ 1 + i ; | 2 + 2i | ] |
|
I J Good (1993) |
√ | 1 + i/2 |
= ( √ |
√5 + 2 |
+ i √
| √5 − 2 | ) /2 |
|
= ( Phi3/2 + i phi3/2 ) /2 |
|
|
|
I J Good (1993) |